Assessing Verb‐Construction Integration in Young Learners of English as a Foreign Language: Analyses of Written and Spoken Production. Issue 2 (24th February 2022) - Kim, Hyunwoo; Hwang, Haerim
Abstract: Extending previous findings on adult L2 learners' integration of verbal and constructional information, this study investigated how child learners of English as a foreign language produce verbs in target constructions and whether (a) receptive skills and (b) the specific production modality (spoken versus written) modulate the integration process. Written and spoken samples from 76 Korean‑speaking children were analyzed for verb‐construction association strength using three independent measures. A mixed‐effects regression analysis showed that the written data contained fewer strongly associated verb‐construction combinations than did the spoken data, yet verb‐construction association in writing became stronger as the participants' receptive task scores increased. Subsequent cluster analyses revealed that the stronger verb‐construction associations found for increasing receptive skills in writing were due to the lower‐proficiency participants' matching some verbs with inappropriate constructions. The modulating role of production modes, as well as receptive skills, in children's integration of verbs and constructions is consistent with usage‐based approaches to language learning. Abstract :